Professores(as) pomeranos(as) : um estudo de caso sobre o Programa de Educação Escolar Pomerana-PROEPO desenvolvido em Santa Maria de Jetibá-ES - Hartuwig, Adriana Vieira Guedes (2011)
This investigation analysis the meaning of the political and pedagogical actions developed by the Pomeranian teachers from the (Programa de Educação Escolar Pomerana - Proepo), in Santa Maria de Jetiba in the state of Espirito Santo. Relate the creation of Proepo, to the multiculturalism debate that in the last few years has acquired visibility, in local and global settings. The development of the process of investigation has benefitted from case studies. The collection of data was done through a series of interviews semi-structured by Pomeranian teachers recorded in audio format, participatory observations in encounters of formation and analysis of documents. Research allows us to state that Proepo is a bilingual formation implemented, in 2005 through a partnership between five local governments from the state of Espírito Santo: Santa Maria de Jetibá, Domingos Martins, Laranja da Terra, Vila Pavão and Pancas. Its main objective is to develop in public school a pedagogical project that values and strengths the Pomeranian culture and language, represented by the oral and written language, dances, religion, architecture and other traditions. Throughout the development of Proepo were obtained important conquests: creation of the Municipal Commission for Linguistic Policy; approval of Municipal Law de Cooficializacão of the Pomeranian language and realization of the language census, still in progress. The Proepo is a partnership experience that contributes in the questioning of the formative process of the bases that neglect the differences, trying to assemble all to one culture and one general language. The strengthening and appreciation of the culture is comprehended by the Proepo teachers as an educative necessity that improves the self-esteem of the students and rescues the historical and cultural aspects of the Pomeranian community, with important impacts on the implementation of local, cultural and public policies